Performance of solid and cellular structured fly ash geopolymers exposed to a simulated fire - Rickard, William; Van Riessen, Arie (Elsevier BV, 2013)
This paper reports on the effects of simulated fire exposure on solid and low density, cellular structured geopolymers in order to assess their suitability for high temperature applications such as thermal barriers and fire resistant panels. Geopolymer mixes with designed Si:Al ratios of 2.5 were synthesised from three different class F fly ashes. Low density samples were produced by adding a small amount of metallic aluminium to the geopolymer slurry which reacted with the free NaOH to produce a cellular structure in the hardened material. Physical properties of the materials are presented as well as results from scale fire tests. An international standard fire curve (ISO 834) was used to simulate the heating conditions of a fire. Fire testing was conducted on 50 mm thick panels with an exposure region of 200 mm × 200 mm. Fire ratings of more than 90 min were achieved with water content and resistance to shrinkage cracking identified as important sample parameters.